Why morphology matters: the negative consequences of hasty descriptions of putative novelties in asexual ascomycetes - Ondřej Koukol; Gregorio Delgado (IMA Fungus, 2021)
ABSTRACT Recent progress in the discovery of fungal diversity has been enabled by intensive mycological surveys in centres of global biodiversity. Descriptions of new fungal species have been almost routinely based on phenotypic studies coupled with single or multigene phylogenetic analyses of DNA sequence data. However, high accessibility of sequencing services together with an increasing amount of available molecular data are providing easier and less critical support for taxonomic novelties without carefully studying the phenotype, particularly morphology. As a result, the accelerated rate of species descriptions has been unfortunately accompanied by numerous cases of overlooking previously described and well documented species, some of them that have been known for more than a century. Here, we critically examined recent literature, phenotypic and molecular data, and detected multiple issues with putative novelties of asexual Ascomycota traditionally known as hyphomycetes. In order to fix these taxonomic problems, three new combinations within the genera Pleopunctum, Camposporium and Sporidesmium, and two new names in Camposporium are proposed. Moreover, three genera, Aquidictyomyces, Fusiconidium and Pseudohelminthosporium, together with nine species are reduced to synonymy. The examples outlined here clearly show the relevance of morphology in modern phylogenetic studies and the importance of more stringent ‘quality controls’ during biodiversity studies documenting the extensive fungal diversity in a speedy manner.